2012
DOI: 10.1073/pnas.1013267109
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution imaging of HIV in infected cells with FlAsH-PALM

Abstract: Imaging protein assemblies at molecular resolution without affecting biological function is a long-standing goal. The diffractionlimited resolution of conventional light microscopy (∼200-300 nm) has been overcome by recent superresolution (SR) methods including techniques based on accurate localization of molecules exhibiting stochastic fluorescence; however, SR methods still suffer important restrictions inherent to the protein labeling strategies. Antibody labels are encumbered by variable specificity, limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 50 publications
(94 reference statements)
6
135
0
2
Order By: Relevance
“…3E) was analyzed to extract information on area and circularity of these adhesive patches (Fig. S10) (25). As expected, β1 integrins on WT thymocytes formed a dense and circular cluster geometry that was independent of sema3E binding.…”
Section: Resultsmentioning
confidence: 99%
“…3E) was analyzed to extract information on area and circularity of these adhesive patches (Fig. S10) (25). As expected, β1 integrins on WT thymocytes formed a dense and circular cluster geometry that was independent of sema3E binding.…”
Section: Resultsmentioning
confidence: 99%
“…However, GFP-Vpr dissociates from the RTCs/PICs shortly after infection and has not been observed in the nuclei of infected cells (33,36,37). To date, only a small number of studies have detected PICs in the nuclei of infected cells by using virions labeled with fluorescently tagged IN (38)(39)(40)(41), and one recent study showed that there are nuclear IN complexes that are not associated with viral cDNA (42), suggesting that fluorescently tagged IN may not be a suitable marker for labeling PICs in the nuclei. Analysis of the nuclear import of PICs has largely relied on quantification of 2-LTR circles, which requires completion of reverse transcription (43).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 virions labeled with fluorophores were pivotal in shedding light onto multiple aspects of the virus-host interplay during all steps of HIV-1 replication cycle (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Nevertheless, few optical approaches have been so far developed to visualize viral particles within the nuclear compartment (14,15), which limits our comprehension of the interaction between HIV-1 and the nuclear architecture.…”
mentioning
confidence: 99%